Interaction between brain L-type calcium channels and alpha(2)-adrenoceptors in the inhibition of sodium appetite - De Luca, L. A.; Sugawara, A. M.; Pereira, DTB; David, R. B.; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2002)
Calcium channels mediate the actions of many drugs. The present work investigated whether diltiazem, an L-type calcium channel blocker, alters the inhibition of sodium appetite induced by noradrenaline and the alpha(2)-adrenoceptor agonist clonidine. Adult male Holtzman rats (N=4-8) with cannula implanted into the third cerebral ventricle were submitted to sodium depletion {furosemide sc+24-h removal of ambiente sodium). Sodium depleted control animals that received 0.9% NaCl as vehicle injected intracerebroventricularly (i.c.v) ingested 13.0+/-1.5 ml/120 min of 1.8% NaCl. Intracerebroventricular injection of either noradrenaline (80 nmol) or clonidine (20 nmol) inhibited 1.8% NaCl intake from 70 to 90%. Prior i.c.v. injection of diltiazem (6-48 nmol) inhibited from 50 to 100% the effect of noradrenaline and clonidine in a dose-response manner. Diltiazem alone at 100 nmol inhibited, but at 50 nmol had no effect on, sodium appetite. The results suggest: (1) common ionic mechanisms involving calcium channels for the inhibition that noradrenaline and clonidine exert on sodium appetite and (2) a dual role for the benzothiazepine site of L-type calcium channels in the control of sodium appetite. (C) 2002 Elsevier B.V. B V. All rights reserved.
Keywords: diltiazem; clonidine; noradrenaline; dehydration; sodium depletion; salt intake